Postcopulatory sexual selection is associated with sperm aggregate quality in Peromyscus mice. (25th September 2021) - Hook, Kristin A; Weber, W David; Fisher, Heidi S
Abstract: In some species, sperm form coordinated groups that are hypothesized to improve their swimming performance in competitive contexts or to navigate through the viscous fluids of the female reproductive tract. Here we investigate sperm aggregation across closely related species of Peromyscus mice that naturally vary by mating system to test the predictions that sperm aggregates 1) are faster than solitary sperm in species that females mate multiply to aid cells in sperm competition, and 2) outperform solitary sperm cells in viscous environments. We find significant variation in the size of sperm aggregates, which negatively associates with relative testis mass, a proxy for sperm competition risk, suggesting that postcopulatory sexual selection has a stabilizing effect on sperm group size. Moreover, our results show that sperm aggregates are faster than solitary sperm in some, but not all, species, and this can vary by fluid viscosity. Of the two species that produce the largest and most frequent groups, we find that sperm aggregates from the promiscuous P. maniculatus are faster than solitary sperm in every experimentally viscous environment but aggregation provides no such kinematic advantage under these same conditions for the monogamous P. polionotus . The reduced performance of P. polionotus aggregates is associated with less efficient aggregate geometry and the inclusion of immotile or morphological abnormal sperm. Our cross-species comparison yields insight into the evolution of sperm social behaviors, provides evidence of extensive variation in the Peromyscus lineage, and reveals that differences in sperm aggregate quality associate with postcopulatory sexual selection. Abstract : It only takes one sperm to fertilize an egg, yet in some species, sperm migrate as a collective group; why they do so remains unclear. Here, we show that aggregation can improve sperm motility for species of deer mice that experience sperm competition, especially in viscous fluids, but this is only true when sperm groups have an efficient architecture. We find evidence that in species with relaxed postcopulatory sexual selection, less efficient strategies persist.